(untitled) (Development Service Industry Management, 2025)
The article is dedicated to studying the development trends of cultural and educational tourism in Western Ukraine under the conditions of the Russo-Ukrainian war, using the example of the tourism organization «Vidviday». The current state of cultural and educational tourism in Western Ukraine is analyzed, with particular attention to the impact of the war on the region’s tourism industry. The activities, financial and economic indicators, and existing offerings of «Vidviday» are examined. The research identifies key development trends in cultural and educational tourism, conducts a SWOT analysis and PEST- analysis of this sector in Western Ukraine, and highlights its strengths and weaknesses, as well as potential threats and opportunities affecting its development. The main challenges, solutions, and development prospects for this type of tourism in the region are outlined. A development strategy for cultural and educational tourism in Western Ukraine has been formulated, taking into account sustainable development factors and adaptation to wartime conditions. Recommendations are provided for improving the use of cultural and educational resources in the region to preserve cultural heritage and enhance the region’s tourism appeal. Thus, cultural and educational tourism contributes to the preservation and promotion of the country’s cultural heritage. New tourist routes focus on lesser-known but significant cultural sites, national identity, and unity during a challenging period for the country.